2017
DOI: 10.3389/fpubh.2017.00225
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects and Public Health Concerns of Energy Drink Consumption in the United States: A Mini-Review

Abstract: As energy drink consumption continues to grow worldwide and within the United States, it is important to critically examine the nutritional content and effects on population health of these beverages. This mini-review summarizes the current scientific evidence on health consequences from energy drink consumption, presents relevant public health challenges, and proposes recommendations to mitigate these issues. Emerging evidence has linked energy drink consumption with a number of negative health consequences s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
77
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 67 publications
3
77
0
2
Order By: Relevance
“…(17) Caffeine intake varies across different types of beverages and in different population groups. (16) The American National Coffee Association (NCA) reported that in 2007, 37% of [18][19][20][21][22][23][24] year olds drank coffee, an increase from 26% in 2005. Young people often consume coffee drinks in large amounts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) Caffeine intake varies across different types of beverages and in different population groups. (16) The American National Coffee Association (NCA) reported that in 2007, 37% of [18][19][20][21][22][23][24] year olds drank coffee, an increase from 26% in 2005. Young people often consume coffee drinks in large amounts.…”
Section: Introductionmentioning
confidence: 99%
“…(22) There is lack of data regarding the possible physical consequences of caffeinated beverages and a clearer understanding is needed about the reasons why young people use energy drinks and the contexts in which they are used. (23) The aim of the study was to estimate the proportion of caffeine consumption among Alexandria University students, to assess their caffeine daily intake in relation to the safety level suggested by the European Food Safety Authority (EFSA), to detect the proportion of caffeine withdrawal and intoxication among caffeine consumers and to investigate the relationship between caffeine intake with body composition, blood pressure, and withdrawal and intoxication symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…La popularidad de las BE ha aumentado desde 1960 cuando se introdujo en el mercado Europeo y Asiático, convirtiéndose en una industria global multimillonaria (2,3). En Latinoamérica, el 64.9% de personas han ingerido BE, siendo principales consumidores, personas entre 13 y 35 años, destacando estudiantes universitarios, trabajadores de oficina y atletas; quienes adujeron las siguientes razones para consumirlas: aliviar la fatiga, mantener la vigilia, mejorar el rendimiento físico y cognitivo ante situaciones de estrés (4).…”
Section: Introductionunclassified
“…Recent studies have suggested that consumption of EDs alone or combined with alcohol leads to oxidative stress and inflammatory response in the brain [4][5][6] . These processes are regulated by a reactive astrogliosis and an increase of proinflammatory cytokines, which trigger neuronal death [4] .…”
Section: Introductionmentioning
confidence: 99%